Role of pulmonary rehabilitation in chronic obstructive pulmonary disease - a historical perspective - Stavarache, Ioan Emanuel; Buculei, Ioana; Cernomaz, Andrei; Vicol, Cristina; Crișan Dabija, Radu Adrian; Trofor, Antigona Carmen (Medicine and Pharmacy Reports, 2022)
Introduction. Pulmonary rehabilitation is known as an effective therapy for patients with chronic obstructive pulmonary disease (COPD). This article is a brief introduction into the history of medical and pulmonary rehabilitation, presenting the evolution of applied therapies and methods from ancient to present times. It also highlights the role of physical effort in the prevention and treatment of lung diseases, with special consideration to COPD. Methods. For this literature review, the international databases Medline and Scopus were used to identify relevant articles, between January 1981 to December 2021; eighty articles were considered: thirty-six reviews, eight original research and six general articles which met the criteria for inclusion. A total of thirty references were excluded because they were not relevant. Results. Available published data suggest a rich history of rehabilitation reaching for thousands of years even though it was developed as a medical branch only in the 20th century. Pulmonary rehabilitation is currently an important component of the management of COPD patients, with a positive impact on symptoms, frequency of exacerbations, severity and mortality rates. Conclusions. Even though this type of intervention is known to be beneficial for this type of patients more studies need to be conducted in this field.